Impact of cluster frontline demonstration on green gram (Vigna radiata L.) Production and contraints in Sikar District semi arid region of Rajasthan - Lala Ram; B.L. Asiwal; Harphool Singh; Jitendra Kumar (Annals of Agricultural Research, 2023)
Green gram (Vigna radiata L.) is one of the most important short-duration pulse crop in India and plays a significant role in the improvement of soil fertility. Front line demonstration is an appropriate means for demonstration of improved technology and innovations in agriculture for large-scale popularization among the farming community. National Food Security Mission, a centrally sponsored scheme on Pulses, enabled KVK, Sikar to conduct Cluster Front Line Demonstrations on Green gram crop during 2016 to 2021 in 475 demonstration plots in 190 ha, not only to demonstrate improved technology for the yield enhancement with quality but to expand the area under crops (Pulse production) as Sikar district is dominated by Pearl millet crop.The present study was conducted in four blocks namely Dhod, Piprali, Laxmangarh and Fatehpur inSikar district of Rajasthan because maximum area sown under green gram. The findings of the study revealed that the demonstrated technology resulted in a mean yield of 9.28 q/ha as compared to farmers practices 7.64 q/ha. The average yield increased 21.30 per cent over farmer’s practices during the six years. The result indicated that the front line demonstration has given a good impact on the farming community of the district about 10.97 q/ha. The higher average gross returns (Rs. 61114 /ha), net return (Rs. 42689/ ha) and effective gain (Rs. 6222/ha) with cost: benefit ratio (3.36) compared to farmers practice as gross return (Rs. 50675/ ha) and net return (Rs. 34358/ ha) with a higher cost: benefit ratio (3.11). The most important constraints ‘lack of knowledge about integrated pest management’faced by 91.20 %, followed by high cost fungicides and pesticides (86.40%), lack of knowledge about proper seed treatment (77.60%), high cost of fertilizers (76.80%), lack of knowledge about proper seed rate (72.0%), lack of knowledge about improved varieties (67.20%) and erratic rainfall in the area (65.6%) were reported by green gram growers in rainfed situation. These constraints were responsible for partial and non-adoption of the improved package of practices of green gram in the district.